Co-occurrence of Lactobacillus Species During Fermentation of African Indigenous Foods: Impact on Food Safety and Shelf-Life Extension - Adesulu-Dahunsi, Adekemi Titilayo; Dahunsi, Samuel Olatunde; Ajayeoba, Titilayo Adenike (Frontiers in Microbiology, 2022)
The benefits derived from fermented foods and beverages have placed great value on their acceptability worldwide. Food fermentation technologies have been employed for thousands of years and are considered essential processes for the production and preservation of foods, with the critical roles played by the autochthonous fermenting food-grade microorganisms in ensuring food security and safety, increased shelf life, and enhanced livelihoods of many people in Africa, particularly the marginalized and vulnerable groups. Many indigenous fermented foods and beverages of Africa are of plant origin. In this review, the predominance, fermentative activities, and biopreservative role of Lactobacillus spp. during production of indigenous foods and beverages, the potential health benefit of probiotics, and the impact of these food-grade microorganisms on food safety and prolonged shelf life are discussed. During production of African indigenous foods (with emphasis on cereals and cassava-based food products), fermentation occurs in succession; the first group of microorganisms to colonize the fermenting substrates are lactic acid bacteria (LAB) with the diversity and dominance of Lactobacillus spp. The Lactobacillus spp. multiply rapidly in the fermentation matrix, by taking up nutrients from the surrounding environments, and cause rapid acidification in the fermenting system via the production of organic compounds that convert fermentable sugars into mainly lactic acid. Production of these compounds in food systems inhibits spoilage microorganisms, which has a direct effect on food quality and safety. The knowledge of microbial interaction and succession during food fermentation will assist the food industry in producing functional foods and beverages with improved nutritional profiling and technological attributes, as Lactobacillus strains isolated during fermentation of several African indigenous foods have demonstrated desirable characteristics that make them safe for use as probiotic microorganisms and even as a starter culture in small- and large-scale/industrial food production processes.